2017
DOI: 10.1111/ddg.13036
|View full text |Cite
|
Sign up to set email alerts
|

S1 guidelines: Lipedema

Abstract: The present, revised guidelines on lipedema were developed under the auspices of and funded by the German Society of Phlebology (DGP). The recommendations are based on a systematic literature search and the consensus of eight medical societies and working groups. The guidelines contain recommendations with respect to diagnosis and management of lipedema. The diagnosis is established on the basis of medical history and clinical findings. Characteristically, there is a localized, symmetrical increase in subcutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
128
0
18

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(149 citation statements)
references
References 42 publications
(43 reference statements)
3
128
0
18
Order By: Relevance
“…A positive family history suggesting lipoedema is linked to a genetic component has been described in up to 60% of cases . The overall prevalence of lipoedema in the general population is uncertain, and it has been reported to be as low as 0.1%; however, some studies conducted on outpatient's clinics estimate the prevalence to be 7% to 10% . Whereas studies conducted on hospitalised patients demonstrated prevalence percentages between 8% and 18% .…”
Section: Epidemiology and Pathogenesismentioning
confidence: 99%
See 4 more Smart Citations
“…A positive family history suggesting lipoedema is linked to a genetic component has been described in up to 60% of cases . The overall prevalence of lipoedema in the general population is uncertain, and it has been reported to be as low as 0.1%; however, some studies conducted on outpatient's clinics estimate the prevalence to be 7% to 10% . Whereas studies conducted on hospitalised patients demonstrated prevalence percentages between 8% and 18% .…”
Section: Epidemiology and Pathogenesismentioning
confidence: 99%
“…The typical presentation is of a woman with bilateral “stovepipe” enlargement of the legs and without involvement of the feet with a sharp demarcation between normal and abnormal tissue at the ankle, referred to as the “cuff sign.” This is often combined with a symmetrical involvement of arms, particularly the upper arms, with sparing of hands. Lipoedema may be isolated to the arms without involvement of the legs, but it is extremely rare . A characteristic feature of lipoedema is pain; it is described as dull, heavy, and pressing.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 3 more Smart Citations